Fruits, Seeds and Seedlings of Two Indian Dipterocarps - Swarupanandan, K. (Indian Forester, 1987)
The paper describes and illustrates fruits, seeds and seedlings of two Indian dipterocarps, viz Vateria indica and Vatica chinensis.